Use of Favipiravir in Covid-19 Patients: A Narrative Review - Vitarani Dwi Ananda Ningrum; Annisa Fitria; Fadiyah Ulfa Hanur (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2024)
COVID-19 is an acute respiratory disease resulting from the infection of SARS-COV-2 viruses and causes high morbidity, which requires appropriate treatment targets. Favipiravir is an antiviral that selectively inhibits RNA-dependent RNA polymerase (RdRp) of virus. This review aimed to identify several studies that prove the effectiveness and safety of using Favipiravir for COVID-19 patients. The search method used the electronic media PubMed and ScienceDirect with the keywords "Efficacy", "Favipiravir", "Treatment", "Safety", SARS-COV-2", and "Favipiravir induced", accompanied by the addition of the affixes "AND" and "OR" and selection by the publication date starting December 2019. The literature search resulted in eight (8) published articles that met the exclusion and inclusion criteria. The results of the review showed that concurrent administration of Favipiravir and Lopinavir/Ritonavir or Chloroquine, with a dosage of Favipiravir of 3200 mg/day followed by 1200 mg/day each in 2 divided doses, was considered adequate for improving the clinical symptoms of COVID-19 patients with mild-moderate symptoms in early administration. Meanwhile, administering Favipiravir with anti-IL-6 Tocilizumab for patients with severe symptoms showed a fairly good effect. The most frequently reported ADE (adverse drug events) in the use of Favipiravir were hyperuricemia and elevated alanine aminotransferase (ALT) levels. This review concluded that the best clinical response to Favipiravir is shown in COVID-19 patients with mild-to-moderate early symptoms.